SUPERVISI AKADEMIK MELALUI PENDEKATAN KOLABORATIF OLEH KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN GURU DI SD KABUPATEN GROBOGAN - Yari Dwikurnaningsih (Satya Widya, 2018)
ABSTRACT This research aimed to increase the quality of instruction through academic supervision with collaborative approached done by school principlas at SD Negeri Kabupaten Grobogan. This research is a school action research. Kemmis and Taggart model is used in this action research model and it was done in two cycles. In each cycle there are planning, implementation and observation and reflection. There are 10 people who were the subject of the research consist of 1 school principal and 9 teachers of SD Negeri Kabupaten Grobogan. The result of the research shows that the quality of instruction score from cycle I and II had increased. In cycle I the average score is 67,5 and in cycle II it became 90. Steps of academic supervision with collaborative approach includes (1) planning-defining supervision goal, schedule, technique chosen and instruments used; (2) implementation after socaliazation and agreement with teacher, the implementation included examining the learning instruments, observing the learning prosess, doing the assessment of learning; (3) the analysis of supervision result was done by identify the strength and weaknesses of teacher and then drown a concussion. Based on the research result and discussion, it can be concluded that academic supervision done by school principla could increase the quality of teachers’ instruction. Key words: academic supervision, collaborative approach, quality of instruction.